YELLOW CAMELLIAS: A REVIEW OF CHEMICAL CONSTITUENTS AND BIOLOGICAL ACTIVITIES - Thi Diep Trinh (Tạp chí Khoa học Đại học Đà Lạt)
To date, 69 species of yellow Camellia have been found in South China and Vietnam, and they have attracted substantial attention from scientists. Chemical and biological studies have only been carried out on a few species, with the main focus on the Chinese species Camellia nitidissima, but have shown that the main active ingredients of these yellow camellia species include flavonoids, phenolic compounds, saponins, triterpenoids, phytosterols, essential oils, amino acids, and polysaccharides. Many pharmacological studies have proved that the total extracts, fractions, and isolated substances from yellow camellia species possess antioxidant, anticancer, hypolipidemic, hypoglycemic, antiallergic, hepatoprotective, neuroprotective, anxiolytic, and antidepressant activities. This review systematically summarizes recent research results in order to provide a comprehensive and up-to-date understanding of the chemical composition and biological activities of yellow camellia species, creating a basis for research of the yellow camellia species in Vietnam and development of new products from this source.